2014
DOI: 10.3109/13816810.2014.885059
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Structure in Cobalamin C Disease: Mechanistic and Therapeutic Implications

Abstract: A thick surface layer near the optic nerve resembling an immature retina and an initially normal macula that rapidly developed coloboma-like lesions suggest there may be an interference with retinal/foveal development in cblC, a mechanism of maculopathy that may be shared by other early onset retinal degenerations. Photoreceptor loss and inner retinal remodeling confirm associated photoreceptor degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 38 publications
4
22
0
Order By: Relevance
“…These signs often occur before 1 year of age and include manifest nystagmus (16/21 [76%]), macular degeneration (7/21 [33%]), and irregular macula and reduced ERG results (patient 9 at 3 months of age and patient 11 at 1 month of age). An additional rare and severe early manifestation, first reported recently in a patient in the first year of life, 23 is macular coloboma as seen in patient 3 (3 months of age; Table 1). Although coloboma also is seen in some, but not all, older cblC patients as they progress to end-stage macular degeneration (Table 1; Fig 3A), 18 coloboma seen in the first few months of life could represent either very severe degenerative processes, abnormal ocular development at the time of birth, or both.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…These signs often occur before 1 year of age and include manifest nystagmus (16/21 [76%]), macular degeneration (7/21 [33%]), and irregular macula and reduced ERG results (patient 9 at 3 months of age and patient 11 at 1 month of age). An additional rare and severe early manifestation, first reported recently in a patient in the first year of life, 23 is macular coloboma as seen in patient 3 (3 months of age; Table 1). Although coloboma also is seen in some, but not all, older cblC patients as they progress to end-stage macular degeneration (Table 1; Fig 3A), 18 coloboma seen in the first few months of life could represent either very severe degenerative processes, abnormal ocular development at the time of birth, or both.…”
Section: Discussionmentioning
confidence: 84%
“…25 A role for this enzyme in human ocular development is suggested by the recent documentation, via spectral-domain OCT, of ocular changes from infancy to 13 years of age in one c.271dupA (p.R91KfsX14) homozygous patient in whom photoreceptor outer segment loss, thinning of the outer nuclear layer, and a thickened, delaminated inner retina resembling an immature retina were noted. 23 Other investigators have observed progressive degeneration via OCT imaging performed at 4 and 7 months of age. 18 The fact that we and others also have observed similar changes in retinal structure (Fig 4B, C), 18,23 that patients can demonstrate severe disease in infancy, and that comorbid developmental abnormalities exist reinforces the concept that cblC deficiency comprises a developmental, as well as a degenerative phenotype.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Early diagnosis and treatment can improve outcomes but cannot prevent all complications of CblC disease (Rosenblatt et al 1997;Andersson et al 1999;Boxer et al 2005;Smith et al 2006;Thauvin-Robinet et al 2007;Martinelli et al 2011;Aleman et al 2014). Early therapy may be particularly beneficial for late-onset patients, as it can be started prior to the development of any organ damage .…”
Section: Discussionmentioning
confidence: 99%